Studi Alternatif Peningkatan Stabilitas Lereng Jalan Akses (Studi Kasus Proyek Pembangunan Taman Teknologi Turyapada Tower Komunikasi Bali Smart 6.0 Kerthi Bali) - Kurniawan, Ari; B. Mochtar, Indrasurya (Syntax Corporation, 2025)
Information technology is advancing rapidly, especially with digital technology and the Internet of Things becoming highly dynamic. Improvements in information services are also being developed extensively throughout the region to support government programs in information dissemination and equitable development and telecommunications infrastructure. However, not all people can benefit from these technological advances due to limited access to information. The Bali Provincial Government has recognized this limited access, as residents in North Bali lack equal access to information due to limited television broadcasting infrastructure and internet signal issues. To this end, the government has built the Turyapada Technology Park, a Bali Smart 6.0 Communication Tower, which primarily functions as a terrestrial digital television transmitter and telecommunications signal transmitter. The tower was constructed in Pancasari Village, a hilly location at an altitude of 1,525 meters above sea level, considering its potential for broadcast coverage across North Bali. This location presents challenges due to its geological conditions, situated on a ridge with limited land and varying soil conditions. Therefore, this topic was chosen for research on alternatives to improve the slope stability of the Turyapada Tower access road. This study aims to examine the stability of natural slopes from the perspective of conventional geotechnical assumptions and the cracked soil theory of the Geo5 support program.